A rapidly incremented tethered-swimming maximal protocol for cardiorespiratory assessment of swimmers - Filho, Dalton M. Pessôa [UNESP]; Massini, Danilo A. [UNESP]; Siqueira, Leandro O. C. [UNESP]; Santos, Luiz Gustavo A. [UNESP]; Vasconcelos, Camila M. T. [UNESP]; Almeida, Tiago A. F. [UNESP]; Espada, Mário A. C.; Reis, Joana F.; Alves, Francisco B.; Dimenna, Fred J. (MyJove, 2020)
Incremental exercise testing is the standard means of assessing cardiorespiratory capacity of endurance athletes. While the maximal rate of oxygen consumption is typically used as the criterion measurement in this regard, two metabolic breakpoints that reflect changes in the dynamics of lactate production/consumption as the work rate is increased are perhaps more relevant for endurance athletes from a functional standpoint. Exercise economy, which represents the rate of oxygen consumption relative to performance of submaximal work, is also an important parameter to measure for endurance-athlete assessment. Ramp incremental tests comprising a gradual but rapid increase in work rate until the limit of exercise tolerance is reached are useful for determining these parameters. This type of test is typically performed on a cycle ergometer or treadmill because there is a need for precision with respect to work-rate incrementation. However, athletes should be tested while performing the mode of exercise required for their sport. Consequently, swimmers are typically assessed during free-swimming incremental tests where such precision is difficult to achieve. We have recently suggested that stationary swimming against a load that is progressively increased (incremental tethered swimming) can serve as a swim ergometer by allowing sufficient precision to accommodate a gradual but rapid loading pattern that reveals the aforementioned metabolic breakpoints and exercise economy. However, the degree to which the peak rate of oxygen consumption achieved during such a protocol approximates the maximal rate that is measured during free swimming remains to be determined. In the present article, we explain how this rapidly incremented tethered-swimming protocol can be employed to assess the cardiorespiratory capacity of a swimmer. Specifically, we explain how assessment of a short-distance competitive swimmer using this protocol revealed that his rate of oxygen uptake was 30.3 and 34.8 mL∙min-1∙kg-1BM at his gas-exchange threshold and respiratory compensation point, respectively.
Keywords: Biochemistry; Cardiorespiratory assessment; Exercise economy; Gas exchange threshold; Incremental exercise testing; Issue 155; Maximal rate of oxygen consumption; Respiratory compensation point; Swimmers; Tethered swimming